The historical evolution and social transformation of settlements in the mountainous regions of western Guangdong: a case study of Xinyi County, China - Wang, Jin; Han, Jiarui (Frontiers in Environmental Science, 2024)
The formation of China’s territory has a long historical process. Prior research has highlighted the diverse historical development patterns across different regions. To delve deeper into the distinctiveness among regions and their nuanced disparities, the research centers on the settlements within Xinyi County, situated in the mountainous terrain of western Guangdong Province, China. The current study employs the research method of “Backward Observation” by conducting a literature review and utilizing ArcGIS for spatial analysis to investigate the spatial distribution and evolution process of regional settlements in western Guangdong. The results suggest a predominant involvement of the state in propelling the advancement of the indigenous community within Xinyi County, a progression primarily fulfilled by the conclusion of the late Qing and initial Republican eras, guided by the persistent localization and gentrification of migrating populations. Xinyi’s advancement pattern and speed exhibited notable distinctions from neighboring areas within Guangdong Province. This investigation additionally delves into G. William Skinner’s inquiries regarding the exceptional attributes and evolutionary patterns of localities, aligning with the South China School’s viewpoint on the varied nature of regional advancement procedures and cadences. This research on Xinyi’s historical evolution is importance in coordinating the preservation and advancement of historical towns, addressing urban-rural development disparities, and formulating future development strategies.